Differences between problematic internet and smartphone use and their psychological risk factors in boys and girls: a network analysis - Rozgonjuk, Dmitri; Blinka, Lukas; Löchner, Nana; Faltýnková, Anna; Husarova, Daniela; Montag, Christian (Child and adolescent psychiatry and mental health, 2023)
BACKGROUND: Problematic internet and smartphone use are significant health challenges for contemporary adolescents. However, their mutual relationship is unclear because studies investigating these phenomena are scarce. The present study aimed to investigate the psychological risks and protective factors associated with problematic internet and smartphone use. METHOD: A representative sample of Slovak adolescents (N = 4070, Mage = 14.38, SDage = 0.77, 50.5% girls) from the Health Behavior in School-aged Children project was analyzed using network analysis separately for boys and girls. RESULTS: The results showed weak (for boys) and moderate (for girls) associations between problematic internet use and problematic smartphone use. Risk factors showed stronger associations with problematic internet use than problematic smartphone use, with the exception of fear of missing out, which was strongly associated with problematic smartphone use. The central nodes were externalizing problems for boys and internalizing problems, externalizing problems, and resilience for girls. CONCLUSION: The study concluded that while problematic internet use and problematic smartphone use are somewhat related, they differ at the psychological level. In addition, the phenomena are rather different between boys and girls.
Keywords: Problematic smartphone use; Problematic internet use; Psychology risk factors; Network analysis; HBSC